2020
DOI: 10.1002/mus.26786
|View full text |Cite
|
Sign up to set email alerts
|

A new parameter to discriminate amyotrophic lateral sclerosis patients from healthy participants by motor cortical excitability changes

Abstract: Introduction We sought a combination of abnormalities to define a more sensitive measure of cortical excitability in amyotrophic lateral sclerosis (ALS). Methods The automatic threshold tracking method was employed to assess the resting motor threshold, intracortical facilitation (ICF), short‐interval intracortical inhibition (SICI), and short‐interval intracortical faciilitation (SICF) in patients and controls. Results SICF at interstimulus intervals (ISI) between 1 and 1.8 ms and 2 and 3 ms as well as averag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 39 publications
(110 reference statements)
0
6
0
Order By: Relevance
“…TMS studies in humans have also demonstrated ICF (111)(112)(113)(114)122), and Vucic et al reported that the measured reduction in SICI represented degeneration of inhibitory cortical circuits combined with hyperexcitation of highthreshold excitatory pathways (123). More recent work has shown that reduced and altered SICI affects motor cortical circuits in ALS; the study also showed that combining two parameters, short-interval ICF and SICI, increases the utility of SICI for identifying patients with ALS (124). Overall, these results demonstrate that in ALS the imbalance between excitatory and inhibitory circuits in the M1 cortex is based on a combination of increased excitability and decreased inhibition (125).…”
Section: Recurrent and Cortical Inhibitionmentioning
confidence: 91%
“…TMS studies in humans have also demonstrated ICF (111)(112)(113)(114)122), and Vucic et al reported that the measured reduction in SICI represented degeneration of inhibitory cortical circuits combined with hyperexcitation of highthreshold excitatory pathways (123). More recent work has shown that reduced and altered SICI affects motor cortical circuits in ALS; the study also showed that combining two parameters, short-interval ICF and SICI, increases the utility of SICI for identifying patients with ALS (124). Overall, these results demonstrate that in ALS the imbalance between excitatory and inhibitory circuits in the M1 cortex is based on a combination of increased excitability and decreased inhibition (125).…”
Section: Recurrent and Cortical Inhibitionmentioning
confidence: 91%
“…For the assessment of motor cortex excitability it is coupled with the measurement of motor evoked potentials (MEP), recorded from a contralateral innervated muscle (e.g., abductor pollicis brevis muscle) (Vucic et al, 2013). Threshold-tracking TMS: The electromagnetic stimulus intensity required to maintain a target MEP response of 200 µV (motor threshold) is measured, reflecting the excitability of UMN (Fisher et al, 2002;Vucic et al, 2018;Cengiz and Kuruoglu, 2020). Resting motor threshold (RMT): The lowest electromagnetic stimulus intensity required to produce an MEP of at least 50 µV at rest (Rothwell et al, 1999;Rosso and Lamy, 2018).…”
Section: What Is "Excitability" and How Is It Assessed In Humans And mentioning
confidence: 99%
“…Short-interval intracortical inhibition (SICI): Inhibition of the MEP response upon a conditioning stimulus applied at a short latency (7−10 ms) prior to the actual stimulation. It compares the MEP amplitude with and without a preceding subthreshold conditioning stimulus (Wagle-Shukla et al, 2009;Cengiz and Kuruoglu, 2020). Cortical silent-period (CSP) duration: Assessment of the duration a voluntary muscle contraction (as measured be EMG) is interrupted by a previous TMS stimulation (typically 100−300 ms upon TMS stimulation).…”
Section: What Is "Excitability" and How Is It Assessed In Humans And mentioning
confidence: 99%
See 2 more Smart Citations